SHARECROPPING IN ISLAM - Qasim Jabr Hassan al-Sudani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this research, I dealt with the definition of sharecropping, both language and convention. As well as the legitimacy of sharecropping according to the opinions of Islamic jurists, It is permissible to contract sharecropping. And also sharecropping terms, and the proper sharecropping faces. I dealt with the corrupt terms of sharecropping, and the ruling on corrupt sharecropping , sharecropping as language and a terminology sharecropping as language